2 by nehalwan

VIEWS: 1 PAGES: 2

More Info
									3/20/2011                                  NCERT CBSE Math Solutions for Class XI…




                                                                                                                              Close
   Relations and Functions (Math)
                                                                                                                                 X
   Miscellaneous «Prev Page 29 Next»                                                                     Q1 Q2 Q3 Q4 Q5 Q6 Q7 Q8



   Question 2:

   Let f: W → W be defined as f(n) = n − 1, if is odd and f(n) = n + 1, if n is even. Show that f is invertible. Find the
   inverse of f. Here, W is the set of all whole numbers.


                                                                            Like   3 people like this.

            Answer       Discussion        Share



     It is given that:


     f: W → W is defined as


     One-one:

     Let f(n) = f(m).

     It can be observed that if n is odd and m is even, then we will have n − 1 = m + 1.

     ⇒n−m=2

     However, this is impossible.

     Similarly, the possibility of n being even and m being odd can also be ignored under a similar argument.

     ∴Both n and m must be either odd or even.

     Now, if both n and m are odd, then we have:

     f(n) = f(m) ⇒ n − 1 = m − 1 ⇒ n = m

     Again, if both n and m are even, then we have:

     f(n) = f(m) ⇒ n + 1 = m + 1 ⇒ n = m

     ∴f is one-one.

     It is clear that any odd number 2r + 1 in co-domain     is the image of 2r in domain         and any even number 2r in
     co-domain is the image of 2r + 1 in domain .

     ∴f is onto.

     Hence, f is an invertible function.

     Let us define g: W → W as:
…meritnation.com/…/9LxV5TAnkcU8P6B…                                                                                                1/2
3/20/2011                                   NCERT CBSE Math Solutions for Class XI…




     Now, when n is odd:



     And, when n is even:



     Similarly, when m is odd:



     When m is even:



     ∴

     Thus, f is invertible and the inverse of f is given by f—1 = g, which is the same as f.

     Hence, the inverse of f is f itself.




…meritnation.com/…/9LxV5TAnkcU8P6B…                                                            2/2

								
To top